Some Pressing Needs of our Iron and Steel Manufactures.* - A. L. Holley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1876)
IT has been customary at our opening sessions, for the presiding officer to address you on the general development of one or another of our several professions, or upon some important feature of Mining or Metallurgical Engineering. It is somewhat embarrassing to his successor that our former President, Dr. Raymond, expert as he is in every one of these professions, has been accustomed to keep them all, in their turn, prominently before you. In selecting for this occasion a subject necessarily connected with iron and steel, I have thought that a review of these manufactures, with reference to some of their more pressing needs for improvement, will be more timely than a general or statistical paper. I shall endeavor to confine my remarks to a few specific defects of practice and management, and to their equally specific and more or less developed remedies. That serious defects exist ; that they must be remedied ; that the manufacture is indeed already on the verge of transition, will be generally admitted. But it cannot be revolutionized all at once, however desirable the technical results might be, for that would bankrupt the business at large. We cannot afford to pull down and rebuild all our blast-furnaces that do not make a ton of pig iron with 25 cwt. of fuel ; nor to replace all our hand-puddling furnaces with revolving ones, even if we could select the best revolver. Although the soft steels promise to supplant iron for most structural purposes, there are neither money nor present market to warrant all at once replacing our iron works, or half of them, with steel works. Since, then, these manufactures can neither standstill nor be suddenly metamorphosed, their managers are saying to one another " We must feel our way into larger development ; we must work gradually into better practice; we must improve a little at a time." * President's address on the opening of the Cleveland meeting.